232k views
8 votes
Which of the following is equivalent to the expression?

Which of the following is equivalent to the expression?-example-1
User Ben Avery
by
5.9k points

2 Answers

8 votes

Answer:

d

Explanation:

- 5 (3x - 7) ← multiply each term in the parenthesis by - 5

= - 15x + 35

User Ruhith Udakara
by
5.9k points
9 votes

Answer: d.) -15x + 35

Given expression:

⇒ -5(3x - 7)

Apply distributive method: a(b + c) = ab + ac

⇒ -5(3x) -5(-7)

multiply the variables

⇒ -15x + 35

User Lewaa
by
5.9k points